Tissue factor–bearing exosome secretion from human mechanically stimulated bronchial epithelial cells in vitro and in vivo - Park, Jin-Ah; Sharif, Asma S.; Tschumperlin, Daniel J.; Lau, Laurie; Limbrey, Rachel; Howarth, Peter; Drazen, Jeffrey M. (Journal of allergy and clinical immunology, 2012)
Tissue factor (TF), a primary initiator of blood coagulation, also plays a pivotal role in angiogenesis. TF expression in the airways is associated with asthma, a disease characterized in part by subepithelial angiogenesis. To determine potential sources of TF and the mechanisms of its availability in the lung microenvironment. Normal human bronchial epithelial cells grown in air-liquid interface culture were subjected to a compressive stress of 30 cm H2O; this is comparable to that generated in the airway epithelium during bronchoconstriction in asthma. Conditioned media and cells were harvested to measure TF mRNA and TF protein. We also tested bronchoalveolar lavage fluid and airway biopsies from asthmatic patients and healthy controls for TF. TF mRNA was upregulated 2.2-fold after 3 hours of stress compared with unstressed cells. Intracellular and secreted TF proteins were enhanced 1.6-fold and more than 50-fold, respectively, compared with those of control cells after the onset of compression. The amount of TF in the bronchoalveolar lavage fluid from patients with asthma was found at mean concentrations that were 5 times greater than those of healthy controls. Immunohistochemical staining of endobronchial biopsies identified epithelial localization of TF with increased expression in asthma. Exosomes isolated from the conditioned media of normal human bronchial epithelial cells and the bronchoalveolar lavage fluid of asthmatic subjects by ultracentrifugation contained TF. Our in vitro and in vivo studies show that mechanically stressed bronchial epithelial cells are a source of secreted TF and that exosomes are potentially a key carrier of the TF signal.